Green design : design for the environment - Mackenzie, Dorothy (London : L. King, 1997)
Green Design sets out to define clearly the issues designers face in making environmental considerations an integral part of the design process, and addresses the problems they may encounter in architecture and interior design; product design; packaging; print and graphics, and textiles
An environmental approach in the whole design-to-production cycle means that decisions must be made about choice of material, minimisation of resources, type of energy source, industrial treatments, the length of life of products, and how to dispose of them when they are no longer of use
Comprehensively revised to take account of recent developments, Green Design reports on the progress made in the area in the last five years, and provides updated guidelines for the design and manufacture of environmentally responsible goods
1. Introduction -- 2. The background to environment issues -- 3. Architecture and interior design -- 4. Product design -- 5. Packaging design -- 6. Print and graphic design -- 7. Textile design -- 8. Changing face of design
Includes bibliographical references (page 170) and index
Keywords: Engineering design; Environmental engineering; Industrial design; Green products